DEVELOPMENT OF CYCLIC VOLTAMMETRIC METHOD FOR THE STUDY OF THE INTERACTION OF ANTIOXIDANT STANDARDS WITH SUPEROXIDE ANION RADICALS CASE OF α-TOCOPHEROL - TOUHAMI LANEZ; MERIEM HENNI; HADIA HEMMAMI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2015)
This work aims to develop a cyclic voltammetry based assay for the calculation of binding parameters like binding constant, ratio of binding constants, and binding free energy of the free and superoxide anion radical bound forms of α-tocopherol (TOC) antioxidant standard. The determination of binding constant is based upon the decrease in anodic peak current of the redox couple in the presence of antioxidant standard, whereas the mode of interaction is concluded from the shift in peak potential values. The diffusion coefficients of both free superoxide anion radical and its bounded forms with TOC were also evaluated from Randles-Sevcik equation.